Tidak Adanya Upaya Resistensi pada Tokoh dalam Novel Permulaan Sebuah Musim Baru di Suriname - MUNA ALFADLILAH (Pendidikan Bahasa dan Sastra Indonesia, 2024)
Novels, especially Dutch East Indies literature, depict the long history of Dutch colonization in Indonesia. Dutch East Indies literature is simply Dutch-language literature that talks about the Dutch East Indies at the time. The book Permulaan Sebuah Musim Baru di Suriname tells the story of Werk, an often dishonest job seeker who often recruits contract workers. In addition, they also often use mysticism and the occult to participate in the selection process. Prospective workers are often attracted by grandiose promises. Groups of workers also come from India and China. This is a very colorful part of Surinamese society. The researcher uses a social approach to investigate the novel whether there is no effort in life resistance. The researcher used a sociological approach to observe that even though the community already knew what was happening abroad, they did not make an initial protest. In this study, qualitative descriptive analysis was used to provide detailed explanations, including quotes and data relating to the subject matter of the novel. Keywords: Java Etnicity, Hindia Belanda, Resistant.